THE SIGNIFICANCE OF CORPUS-BASED TECHNOLOGIES IN LEARNING AND TEACHING FOREIGN LANGUAGES - Shayusupova, Nargiza Bakhtiyorovna; Shermuminova, Umida Khasan kizi (INTERNATIONAL CONFERENCES, 2023)
This article discusses the importance of Corpora and corpus - based technologies in learning and teaching foreign languages. Using corpora in language teaching has changed language research into new step with its ‘authentic’ appeal. With the use of corpus technologies, linguistic researchers and educators can now analyze usages and the features of particular genres to enhance syllabus design and determine more productive classroom activities.